Brain-Derived Neurotrophic Factor (BDNF) Serum and Intelligence Levels of Elementary School Children in Rural Areas, Seluma Regency (Jurnal Ilmu Kesehatan Masyarakat, 2021)
Children living in rural areas are prone to nutritional deficiencies. Low-income levels impact people’s purchasing power so that the intake of most nutrients comes from plant-based foods and consumes less animal food. Nutritional intake greatly affects the development of children’s cognitive function. Brain-derived neurotrophic factor (BDNF) is a group of neurotrophins that contribute greatly to the learning process and memory. This study aims to analyze the relationship between levels of BDNF with the level of intelligence in elementary school children in rural areas of Seluma Regency. This was a cross-sectional study involving 70 elementary school children aged 9-12 years were taken by multi-stage random sampling, who came from 5 districts of Seluma Regency. Blood was collected for measurement of BDNF levels, and stool samples were examined to detect intestinal parasites. The data on respondent characteristics were derived from questionnaires.  Data analysis were done by using the chi-square test. The results of BDNF measurements found 31 children (44.3%) had BDNF levels below the average (<3342.95ng / mL). The results of measuring intelligence level found that 54 children (77.1%) had a level of intelligence below the average. Chi-Square test results obtained p = 0.012 with a PR value of 7.538. There was a significant  association between the BDNF level and intelligence level in elementary school students in the rural area. Elementary school children in rural areas with BDNF levels below the average risk of 7.538 times have below-average intelligence levels.